ANALISIS YURIDIS TERHADAP PERTIMBANGAN HUKUM OLEH HAKIM PENGADILAN AGAMA KABUPATEN MALANG TENTANG DISPENSASI NIKAH (STUDI PENETAPAN NO. 1564/Pdt.P/2020/PA.Kab.Mlg) - Mas Hadi Malik Al Mustofa; Ach. Faisol; Syamsu Madyan (Jurnal Hikmatina, 2021)
A judge in deciding a case must include considerations in the determination or decision that is produced. Legal considerations are also required in the case of a marriage dispensation application. This study aims to describe how a judge considers a marriage dispensation application submitted to the Malang Regency Religious Court to be granted or rejected. Also to find out how the juridical analysis of the determination resulted from these considerations. This research was conducted using qualitative methods. The results obtained by the researcher that the legal considerations by the Malang Regency Religious Court judges on the application for marriage dispensation are judges in handling marriage dispensation cases based on Supreme Court Regulation Number 5 of 2019. By referring to PERMA, it was found that the applicant was worried about the occurrence of something prohibited by religion if the child is not immediately married, because the applicant's child has been engaged to his partner for 2 years. The judge considered that both of them were ready to build a household, and if the marriage was not carried out immediately it would cause greater harm. The stipulation given also has basic legal values including legal certainty, justice, and benefit both to the parties concerned and to the community.